Essential Oils Activity of Legundi Leaf (Vitex trifolia L.) as A Repellent for Rice Weevil (Sitophilus oryzae) - Jayuska, Afghani; Warsidah, Warsidah; Asikin, Nurul; Widiyantoro, Ari; Aritonang, Anthoni B. (Universitas Jember, 2022)
Legundi (Vitex trifolia L.) is a plant that contains essential oils. Legundi leaf essential oil has the potential as a more environmentally friendly rice lice repellent. The process of extracting essential oils from Legundi leaves uses the steam-water distillation method. The yield obtained from distillation is 0.10% with a bright yellow color, has a distinctive smell of Legundi oil with a specific gravity of 0.9065 gram/cm3. GC-MS search results showed that Legundi leaf essential oil contains 5 main components, namely 2-β-Pinene (16.18 %), trans-caryophyllene (13.75 %), β-Ocimene (11.16 %), Cyclohexanol (10.03%), and Eucalyptol (5.45%). Testing of repellent activity was carried out on rice lice with variations in volatile oil concentrations of 1%, 5%, 10%, and 20%. The results of the repellent test showed that the highest percentage occurred at a concentration of 20% (P4), which was 56.7%, with an application time of 120 hours (L5). Based on this, it can be said that the greater the concentration of the essential oil used, the higher the percentage of rejection of the population, this also indicates that Legundi leaf essential oil has lice repellent activity (Sitophilus oryzae).